Tra comprensibile e incomprensibile: il delirio di riferimento sensitivo - Gebhardt, Eva; Amorini, Anna (Il sogno della farfalla, 2020)
In this article the authors analyze Ernest Kretschemer’s theoretical work on delusion. Contrary to organicist and categorical ideas, based on Kraepelin’s view, Kretschemer is among the authors who particularly strove to provide a psychogenetic understanding of psychosis and of its related psychicreactive manifestations. Although his theory had been criticized and underestimated for many years, his ideas have considerably influenced the progress of psychiatry.